Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Sure, let’s work through this problem step by step.
### Part a) Factorizing the Expression [tex]\(2x^2 + 11x + 5\)[/tex]
We need to factorize the quadratic expression [tex]\(2x^2 + 11x + 5\)[/tex]. We will find two binomials that, when multiplied, give us the original quadratic expression.
Given:
[tex]\[ 2x^2 + 11x + 5 = (2x + \square)(x + \square) \][/tex]
To determine the values that fill in these squares, consider the factored form.
From the result, we know the factors are:
[tex]\[ (2x + 1)(x + 5) \][/tex]
So, filling in the squares, we get:
[tex]\[ 2x^2 + 11x + 5 = (2x + 1)(x + 5) \][/tex]
### Part b) Solving the Equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex]
Now that we have the factorized form from part a), we can use it to solve the equation:
[tex]\[ 2x^2 + 11x + 5 = 0 \][/tex]
Substituting the factored form, we get:
[tex]\[ (2x + 1)(x + 5) = 0 \][/tex]
To find the values of [tex]\(x\)[/tex], we set each factor equal to zero and solve:
1. For [tex]\(2x + 1 = 0\)[/tex]:
[tex]\[ 2x + 1 = 0 \][/tex]
[tex]\[ 2x = -1 \][/tex]
[tex]\[ x = -\frac{1}{2} \][/tex]
2. For [tex]\(x + 5 = 0\)[/tex]:
[tex]\[ x + 5 = 0 \][/tex]
[tex]\[ x = -5 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex] are:
[tex]\[ x = -5 \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
### Summary
a) The factorized form of the quadratic expression is:
[tex]\[ 2x^2 + 11x + 5 = (2x + 1)(x + 5) \][/tex]
b) The solutions to the equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex] are:
[tex]\[ x = -5 \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
### Part a) Factorizing the Expression [tex]\(2x^2 + 11x + 5\)[/tex]
We need to factorize the quadratic expression [tex]\(2x^2 + 11x + 5\)[/tex]. We will find two binomials that, when multiplied, give us the original quadratic expression.
Given:
[tex]\[ 2x^2 + 11x + 5 = (2x + \square)(x + \square) \][/tex]
To determine the values that fill in these squares, consider the factored form.
From the result, we know the factors are:
[tex]\[ (2x + 1)(x + 5) \][/tex]
So, filling in the squares, we get:
[tex]\[ 2x^2 + 11x + 5 = (2x + 1)(x + 5) \][/tex]
### Part b) Solving the Equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex]
Now that we have the factorized form from part a), we can use it to solve the equation:
[tex]\[ 2x^2 + 11x + 5 = 0 \][/tex]
Substituting the factored form, we get:
[tex]\[ (2x + 1)(x + 5) = 0 \][/tex]
To find the values of [tex]\(x\)[/tex], we set each factor equal to zero and solve:
1. For [tex]\(2x + 1 = 0\)[/tex]:
[tex]\[ 2x + 1 = 0 \][/tex]
[tex]\[ 2x = -1 \][/tex]
[tex]\[ x = -\frac{1}{2} \][/tex]
2. For [tex]\(x + 5 = 0\)[/tex]:
[tex]\[ x + 5 = 0 \][/tex]
[tex]\[ x = -5 \][/tex]
Thus, the solutions to the quadratic equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex] are:
[tex]\[ x = -5 \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
### Summary
a) The factorized form of the quadratic expression is:
[tex]\[ 2x^2 + 11x + 5 = (2x + 1)(x + 5) \][/tex]
b) The solutions to the equation [tex]\(2x^2 + 11x + 5 = 0\)[/tex] are:
[tex]\[ x = -5 \quad \text{and} \quad x = -\frac{1}{2} \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.